The role of fatwa and mufti in contemporary Muslim society - Hj Ibrahim, Badruddin; Arifin, Mahamad; Abdul Rashid, Siti Zainab (2015)
Fatwa in general refers to legal opinion issued by any Muslim jurist (mufti) relating to certain ruling of Islamic law. In principle, fatwa serves as a means of clarifying any issue that arises in Muslim Society. This reflects that fatwa and mufti are two crucial significant tools of providing legal guidance within the ambit of the Shari’ah governing Muslim in his day to day affairs. This is because even though fatwa is not legally binding when it is issued, it carries a significant effect in contemporary society as it provides guideline and rule to follow. This paper seeks to examine the significant role of fatwa and mufti respectively in contemporary Muslim society. Discussion will include definition of fatwa, historical background on development of fatwa, conditions of fatwa, qualification of person who is eligible to issue fatwa, scope and purview of fatwa, legal effect of fatwa on the Muslim community and the role of fatwa and mufti respectively in attending issues and problems arising in contemporary Muslim society. The research will mainly adopt library research in providing a sound legal theory of fatwa under Islamic law. It is believed that the findings of the research will provide a clear guideline relating to the role of fatwa and mufti in the contemporary Muslim society which may benefit the fatwa institution in Malaysia in particular and the public at large.